J Proteomics Bioinform 2020
DOI: 10.35248/0974-276x.1000508
|View full text |Cite
|
Sign up to set email alerts
|

ROS and MAPK Cascades in the Post-harvest Senescence of Horticultural Products

Abstract: Plants are naturally sessile and cannot move away from adverse environmental conditions. Environmental stress may induce loss of membrane integrity, which is a seminal feature of premature senescence. Therefore, plants must respond in other ways to protect themselves from abiotic and biotic stresses that involve protein kinases, which are crucial to signal transduction pathways. Protein kinases are involved in the phosphorylation of serine/threonine and tyrosine side chains of proteins. Among these protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…High temperature affects multiple cellular processes, including photosynthesis, respiration and protein stability, and the disruption of these normal physiological activities leads to an overproduction of ROS and causes oxidative stress ( Kumar, 2012 ; Posch et al., 2019 ; Zahra et al., 2023 ). Previous work has reported that in response to heat stress, MAPK cascade is involved in signal transduction, which affects plant physiological processes, such as photosynthesis, respiration, transpiration, nutrient uptake, tropisms, and senescence ( Lee et al., 2016 ; Chardin et al., 2017b ; Gouda et al., 2020 ; Liu et al., 2020 ). In this study, there was a reduction in contents of H 2 O 2 and MDA, and an increase in antioxidant activities, induced by StMAPKK5 overexpression under heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…High temperature affects multiple cellular processes, including photosynthesis, respiration and protein stability, and the disruption of these normal physiological activities leads to an overproduction of ROS and causes oxidative stress ( Kumar, 2012 ; Posch et al., 2019 ; Zahra et al., 2023 ). Previous work has reported that in response to heat stress, MAPK cascade is involved in signal transduction, which affects plant physiological processes, such as photosynthesis, respiration, transpiration, nutrient uptake, tropisms, and senescence ( Lee et al., 2016 ; Chardin et al., 2017b ; Gouda et al., 2020 ; Liu et al., 2020 ). In this study, there was a reduction in contents of H 2 O 2 and MDA, and an increase in antioxidant activities, induced by StMAPKK5 overexpression under heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also suggested that disease resistance is not closely associated with antioxidant capacity in postharvest jujube fruit. Previous reports showed that free radicals and/or reactive oxygen species (ROS) play a key role in regulating disease resistance 15 , 24 and antioxidant biosynthesis in plants 38 , 39 . Therefore, we explored how these agents affect ROS production and accumulation in postharvest jujube fruit.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to aging acceleration and limitation of shelf life (Mastropasqua et al, 2016). The mechanisms of post-harvest aging and rapid quality loss are associated with the development of oxidative stress (Bata Gouda et al, 2020). Slowing down metabolic processes and the intensity of gas exchange, preventing the development of oxidative stress make asparagus storage effective.…”
Section: Introductionmentioning
confidence: 99%